2014
DOI: 10.6061/clinics/2014(12)10
|View full text |Cite
|
Sign up to set email alerts
|

Glucosamine and chondroitin sulfate association increases tibial epiphyseal growth plate proliferation and bone formation in ovariectomized rats

Abstract: OBJECTIVE:The growth plate consists of organized hyaline cartilage and serves as a scaffold for endochondral ossification, a process that mediates longitudinal bone growth. Based on evidence showing that the oral administration of glucosamine sulfate (GS) and/or chondroitin sulfate (CS) is clinically valuable for the treatment of compromised articular cartilage, the current study evaluated the effects of these molecules on the tibial epiphyseal growth plate in female rats.METHOD:The animals were divided into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 39 publications
(44 reference statements)
1
12
0
Order By: Relevance
“…It should be taken into consideration that the hyaline cartilage structure lacks blood supply, does not contain fibrous connective tissue and has a limited number of progenitor cells. Nevertheless, 60-day combined CS+G treatment in female rats subjected to tibial epiphyseal degeneration by ovariectomy resulted in marked chondrocyte proliferation and significant longitudinal bone growth [50]. In the TMJ, however, fibrocartilage may behave similarly to the perichondrium by becoming a source of mesenchymal cells that are precursors of new chondrocytes [51].…”
Section: Discussionmentioning
confidence: 99%
“…It should be taken into consideration that the hyaline cartilage structure lacks blood supply, does not contain fibrous connective tissue and has a limited number of progenitor cells. Nevertheless, 60-day combined CS+G treatment in female rats subjected to tibial epiphyseal degeneration by ovariectomy resulted in marked chondrocyte proliferation and significant longitudinal bone growth [50]. In the TMJ, however, fibrocartilage may behave similarly to the perichondrium by becoming a source of mesenchymal cells that are precursors of new chondrocytes [51].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing levels of inclusion of chondroitin and glucosamine sulfates in broiler diets increased the frequency of birds without deviations (valgus and varus) and minimize the with gait score. Chondroitin and glucosamine sulfates are nutraceuticals that have the functions to prevent and treat injuries to the locomotor system ( Kamarul et al., 2011 ; Kantor et al., 2014 ; Wolff, 2014 ; Lubis et al., 2017 ) and reduce pain caused by locomotor problems ( Wolff et al., 2014 ). In addition, these glycosaminoglycans modulate the expression of osteoprotegerin and receptor activator of nuclear factor kappa B ligand, the 2 main factors involved in bone remodeling, with a protective effect on bone loss ( Tat et al., 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Polysulfated glycosaminoglycans have prevented and/or reduced the progression of pathologic changes in bone and joint structures of animal models such as rats ( Wen et al., 2010 ; Chiusaroli et al., 2011 ; Jawed et al., 2011 ; Muraleva et al., 2012 ; Arafa et al., 2013 ; Wolff, 2014 ), rabbits ( Herrero-Beaumont et al., 2008 ; Largo et al., 2010 ; Kamarul et al., 2011 ), dogs ( Vieira et al., 2010 ; Eleotéreo et al., 2012 ; Gupta et al., 2012 ; Maxwell et al., 2016 ; Wenz et al., 2017 ), broiler chickens ( Sgavioli et al., 2017 ; Santos et al., 2018 , 2019 ), humans ( Kahan et al., 2009 ; Wildi et al., 2011 ; Kantor et al., 2014 ; Lubis et al., 2017 ), and in vitro ( Tat et al., 2007 ; Varghese et al., 2007 ; Uitterlinden et al., 2008 ; Calamia et al., 2010 , 2012 , 2014 ; Chiusaroli et al., 2011 ; Imagawa et al., 2011 ; Pecchi et al., 2012 ; Cunha et al., 2017 ; Igarashi et al., 2017 ; Kim et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been controversial reports regarding the effect of GA on cell proliferation; while the inhibitory effect of GA on cell proliferation was reported, other groups showed that GA enhance the cell proliferation …”
Section: Resultsmentioning
confidence: 99%